Determination of selected alpha-keto acids in dried blood samples using HPLC with fluorescence detection - Kanďár, Roman; Kopčil, Michal; Laštovičková, Lenka (Elsevier Science Inc., 2022)
The determination of alpha-keto acids derived from amino acids is currently the most reliable approach for the diagnosis of some congenital metabolic diseases. An HPLC method for the simultaneous measurement of selected alpha-keto acids in dried blood samples has been developed and evaluated. Blood spot samples from a group of healthy blood donors were collected onto #903 Specimen Collection Paper. Prior the separation, the alpha-keto acids were derivatized with 1,2-diamino-4,5-dimethoxybenzene to the corresponding 3-substituted-6,7-dimethoxy-2 (1 H)-quinoxalinol derivatives. For the separation, a reverse-phase column LichroCart 125-4, Purospher RP-18e, 5 mu m, was used. The mixture of 25% ACN in deionized water (mobile phase A) and 100% ACN (mobile phase B) were used for a gradient elution of alpha-keto acids derivatives. Analytical performance of this method is satisfactory for all alpha-keto acids. The intra-assay and inter-assay coefficients were below 10% and recoveries were close to 100%. We have developed relatively simple, rapid, selective and sufficiently sensitive HPLC method with fluorescence detection for the determination of selected alpha-keto acids in dried blood samples. The presented method is suitable for clinical testing purposes.
Stanovení vybraných α-oxokyselin ve vzorcích suché krve metodou HPLC s fluorescenční detekcí
Keywords: alpha-Keto acids; dried blood spot; HPLC with fluorescence detection; 1,2-Diamino-4,5-dimethoxybenzene; α-oxokyseliny; suchá kapka krve; HPLC s fluorescenční detekcí; 1,2-diamino-4,5-dimethoxybenzen